Key role of thymic stromal lymphopoietin as a molecular target for biologic treatment of severe asthma - Pelaia, Corrado; Melhorn, James; Paoletti, Giovanni; Poto, Remo; Maglio, Angelantonio; Crimi, Claudia; Vatrella, Alessandro; Canonica, Giorgio Walter; Pelaia, Girolamo (Frontiers in Allergy, 2025)
Thymic stromal lymphopoietin (TSLP) is an alarmin mainly released by airway epithelial cells injured by many environmental noxious agents such as aeroallergens, respiratory viruses, bacteria, airborne pollutants and cigarette smoking. Airway expression levels of TSLP are related to both asthma severity and the extent of bronchial obstruction occurring in asthmatic patients. The pivotal pathogenic role played by TSLP in asthma is due to its capability of acting as an upstream driver of multiple cellular and molecular proinflammatory pathways, responsible for the development and persistence of both type 2 (T2-high) and T2-low asthma. Tezepelumab is a fully human monoclonal antibody which specifically binds to TSLP, thus impeding its interaction with the TSLP receptor complex expressed by immune/inflammatory and resident cells of the airways. By virtue of this very effective mechanism of action, tezepelumab prevents disease exacerbations and improves lung function. These positive outcomes have been verified by randomized clinical trials, as well as by preliminary real-life studies. The aim of this narrative review is to provide an overview of the pathogenic involvement of TSLP in asthma, followed by an updated discussion focused on the therapeutic effects induced by tezepelumab in severe asthmatic patients.